2009
DOI: 10.1063/1.3073653
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic correlations in nanocomposite FePt:Au and FePt:C films

Abstract: The nanostructure and magnetism of L1 0 -ordered FePt crystallites in matrices of Au and C are investigated as a function of the Au and C contents. Emphasis is on the relation between hysteresis-loop shape, magnetic correlation length, and structural disorder, as relevant to magnetic recording media. The highly ͑001͒ textured thin films are produced by annealing ͓Fe/ Pt/ X͔ n multilayers. The coercivity and the hysteresis-loop slope at coercivity increase and decrease, respectively, with increasing volume frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…and analyzed the influence of the introduction of a sublayer or a top layer, in situ annealing, sequential monolayer deposition, decrease in the layer thickness, application of the FePt alloy of nonstoichiometric composition (see [4] and references therein), and ion irradiation [4]. A large variety of substrates and sublay ers, such as MgO, Au, Ag, Pt, CrRu, CrMo, Zr, and RuAl (see [4,11,12] and references therein), have been used to obtain the Ll 0 phase in the FePt (001) textured films suitable for perpendicular magnetic recording. Attempts have been made to decrease the size of grains in the FePt films and to reduce the exchange interaction between the particles by means of the addition of a third element to the FePt nano composite films, namely, Ag, W, Ti, Ni, B, C, N, and others (see [4,[11][12][13][14][15] and references therein).…”
Section: Effect Of Annealing In An Externalmentioning
confidence: 99%
See 1 more Smart Citation
“…and analyzed the influence of the introduction of a sublayer or a top layer, in situ annealing, sequential monolayer deposition, decrease in the layer thickness, application of the FePt alloy of nonstoichiometric composition (see [4] and references therein), and ion irradiation [4]. A large variety of substrates and sublay ers, such as MgO, Au, Ag, Pt, CrRu, CrMo, Zr, and RuAl (see [4,11,12] and references therein), have been used to obtain the Ll 0 phase in the FePt (001) textured films suitable for perpendicular magnetic recording. Attempts have been made to decrease the size of grains in the FePt films and to reduce the exchange interaction between the particles by means of the addition of a third element to the FePt nano composite films, namely, Ag, W, Ti, Ni, B, C, N, and others (see [4,[11][12][13][14][15] and references therein).…”
Section: Effect Of Annealing In An Externalmentioning
confidence: 99%
“…A large variety of substrates and sublay ers, such as MgO, Au, Ag, Pt, CrRu, CrMo, Zr, and RuAl (see [4,11,12] and references therein), have been used to obtain the Ll 0 phase in the FePt (001) textured films suitable for perpendicular magnetic recording. Attempts have been made to decrease the size of grains in the FePt films and to reduce the exchange interaction between the particles by means of the addition of a third element to the FePt nano composite films, namely, Ag, W, Ti, Ni, B, C, N, and others (see [4,[11][12][13][14][15] and references therein). In [16], it was reported that FePt anisotropic films with the (001) texture and FePd/α Fe foils were prepared by cold rolling with the subsequent annealing in a mag netic field.…”
Section: Effect Of Annealing In An Externalmentioning
confidence: 99%
“…The coercivity increase with Hf content is largely a consequence of the reduced magnetization, because H c = 2K/M s [11], with some concentration dependence of . But for the complicated irregular interaction domains, the magnetic correlation length L (the average domain width) can be estimated by several methods [13][14][15][16][17][18]. The magnetocrystalline anisotropy parameter K and the spontaneous magnetization M 0 can be determined by fitting the hysteresis loops using the law of approach to saturation method [12].…”
Section: Resultsmentioning
confidence: 99%
“…They are promising materials for use as high-density recording media [4][5][6]. In this respect, the magnetic and coercive properties of various composites and the relationship of these properties to the morphology and structure of the granules are being actively studied [7][8][9][10][11][12][13][14][15][16][17][18]. The behavior of such films has been studied for both blocked and unblocked states of thermally activated reorientations of the granules' magnetic moments [19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic properties of the films under consideration have been analyzed for magnetization perpendicular or/and parallel to the film plane [7][8][9][10][11][12][13][14][15][16][17][18]. However, as far as we know, the case of film magnetization in an arbitrary direction (inclined magnetization) has been studied insufficiently both experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%